2021
DOI: 10.7759/cureus.17039
|View full text |Cite
|
Sign up to set email alerts
|

Kugel’s Artery: Silent Bystander or Savior?

Abstract: Kugel’s artery is defined as a rare anatomical variant of the coronary artery vascular bed consisting of an anastomotic connection between branches of the right coronary artery (RCA) and/or left circumflex artery (LCX). Kugel’s artery has been reported to have an incidence of 6% in the general population. The presence of this anastomotic communication may play a pathophysiological role in a patient with a right dominant coronary circulation and an underlying coronary artery disease (CAD) affecting the right co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Diagnostic studies revealed a two-vessel disease with a critical distal left main spontaneous coronary artery dissection occluding approximately 90% of the vessel and a critical proximal left anterior descending (LAD) artery stenosis (Figure 1 and Video 1 ). Incidentally, the diagnostic study revealed a Kugel artery which is a rare anatomical variant of the coronary artery vasculature with an anastomotic connection between the RCA and left circumflex artery [ 4 ]. Cardiothoracic and Vascular Surgery was consulted for emergent two-vessel coronary artery bypass grafting (CABG).…”
Section: Case Presentationmentioning
confidence: 99%
“…Diagnostic studies revealed a two-vessel disease with a critical distal left main spontaneous coronary artery dissection occluding approximately 90% of the vessel and a critical proximal left anterior descending (LAD) artery stenosis (Figure 1 and Video 1 ). Incidentally, the diagnostic study revealed a Kugel artery which is a rare anatomical variant of the coronary artery vasculature with an anastomotic connection between the RCA and left circumflex artery [ 4 ]. Cardiothoracic and Vascular Surgery was consulted for emergent two-vessel coronary artery bypass grafting (CABG).…”
Section: Case Presentationmentioning
confidence: 99%